From Traumatic Language to Posttraumatic Language: The Development of Language in Therapy According to the "Phenomenon of Hope" Model. Issue 1 (2nd January 2017) - Levi, Ofir
ABSTRACT: Hope and language are part of the human development process starting from birth and continuing through all the stages of development. They are tools that help us to cope in complex situations. Environmental failure produces trauma, which damages the "self" and impairs the development of hope and language. The individual experiences "pessimistic hope" and "drained hope" and begins using "concrete language" and "pseudo-language." Such profiles and languages indicate functional difficulties, including the inability to establish mature intimate personal relationships. When traumatic events such as those experienced in military combat compound childhood trauma (environmental failure), mental and functional difficulties buried by our defense systems may rise to the surface and worsen and chronic complex trauma may ensue. Psychotherapy for chronic complex trauma is complex. The therapeutic approach that is used in the "hope phenomenon" model includes five therapy stages that allow us to examine the effect of a trauma on personality and function. Here we examine the link between the five stages of therapy and the use of language. According to my experience, patients use concrete language and pseudo-language in the beginning of the therapeutic connection. As this connection and therapist-patient alliance evolves and deepens and the client and therapist move through the various stages, the patient then starts to use "plural language." Concrete language and pseudo-language are used in the pessimistic hope and drawn hope stages, respectively, until a profile characterized by a realistic and mature hope emerges. This profile goes hand in hand with an ability to use plural language. This article examines the development of hope and language in a complex posttraumatic stress disorder (PTSD) patient who was treated using the hope phenomenon model. Consent for the therapy details to be used in this article was given by the patient.